Revising the effectiveness of municipal waste management in Hong Kong - Ma, Fong Ching; Wong, Tsan Lok; Chan, Chun Ngai; Ran, Lishan (Frontiers in Environmental Science, 2023)
Although there have been many studies related to the municipal solid waste (MSW) problem in Hong Kong, only limited research has recently discussed the spatial variation of citizens’ environmental awareness in different geographical constituencies. Also, the relationship between environmental awareness of citizens and the effectiveness of waste management has been poorly understood. This research aims to evaluate the effectiveness of three proposed approaches; investigate whether the environmental awareness of citizens will affect the effectiveness of current waste management strategies; and examine the differences in the level of environmental awareness of residents in different geographical constituencies, so we can provide suggestions to help mitigate the solid waste problem. In addition, the hypothesis is that there is a relationship between environmental awareness of citizens and its effectiveness. This research adopted quantitative observations and questionnaires as well as qualitative interviews to understand the public perception about the proposed MSW charging, plastic shopping bag charging and recycling in Hong Kong. This research confirmed that the environmental awareness of Hong Kong citizens varies among various geographical constituencies. Residents in Kowloon West have comparatively lower environmental awareness may due largely to the socio-economic background of residents and comparatively unhygienic environment, and they often do not support plastic shopping bag charging and recycling. In addition, males have a lower environmental awareness than females as their attitude towards charging policy may not have much impact on their lifestyle. It is not surprising that low environmental awareness of citizens will reduce the effectiveness of current environmental policies. MSW charging tends to be effective and should be implemented in Hong Kong. Furthermore, plastic shopping bag charging can be effective in the short term but ineffective in the long term, and recycling tends to be invalid as Hong Kong has not developed a circular economy. The limitations of each policy should be considered, and more studies are needed to improve the existing policies as well as exploring novel ways to solve the MSW problem.